2022
DOI: 10.1080/13880209.2022.2033275
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin mitigates spermatogenic and redox related expression in H 2 O 2 -exposed Leydig cells and regulates testicular oxidative apoptotic signalling in aged rats

Abstract: Context Cordycepin (COR), from Cordyceps militaris L., (Cordycipitaceae), is a valuable agent with immense health benefits. Objective The protective effects of COR in ageing-associated oxidative and apoptosis events in vivo and hydrogen peroxide (H 2 O 2 )-exposed spermatogenesis gene alterations in TM3 Leydig cells was investigated. Materials and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Therefore, antioxidant treatments may be efficient therapeutic choices for dealing with the burden of oxidative stress-induced male infertility 70 , 74 . In agreement with our finding, pretreatment of rats with other antioxidants [Curcumin, Gallic acid, and/or Nigella sativa oil] before tramadol administration restored such inhibition in antioxidant enzyme activities 10 , 74 , 75 . Therefore, the low number of spermatozoa and testosterone levels in tramadol-treated rabbits could be due to depletion of glutathione levels and inhibition of antioxidant enzyme activity which leads to induction of free radical levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, antioxidant treatments may be efficient therapeutic choices for dealing with the burden of oxidative stress-induced male infertility 70 , 74 . In agreement with our finding, pretreatment of rats with other antioxidants [Curcumin, Gallic acid, and/or Nigella sativa oil] before tramadol administration restored such inhibition in antioxidant enzyme activities 10 , 74 , 75 . Therefore, the low number of spermatozoa and testosterone levels in tramadol-treated rabbits could be due to depletion of glutathione levels and inhibition of antioxidant enzyme activity which leads to induction of free radical levels.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the present study, SOD, CAT, GR, GPx, and GST activities are inhibited in the livers of rats after tramadol treatment 10 . The mechanism of inhibition of antioxidant enzyme activities might be due to the interaction of tramadol or its metabolites with certain metal ions, such as selenium, that function as cofactors for antioxidant enzymes (SOD, GPx) 75 . Supporting this finding from the present study, when selenium was given to rabbits before tramadol therapy was found to increase the activities of SOD, GPx.…”
Section: Discussionmentioning
confidence: 99%
“…The Crocin-treated groups were changed to DMEM medium containing Crocin after H 2 O 2 pretreatment. Drug concentrations were used as per previous studies [ 22 , 23 ]. Cell viability was detected with a 96-well plate and CCK-8 kit.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, testosterone may be helping to limit DNA damage by reducing gonadal NOX activity (especially in dominants), and although it is unclear the extent to which gonadal ROS production might influence global DNA damage, the observed negative relationship between testosterone and NOX activity has previously been observed (Juliet et al, 2004; Tam et al, 2003). Alternatively, given that high levels of oxidative stress can have inhibitory effects on gonadal androgen synthesis (Glade and Smith, 2015; Kopalli et al, 2022; Turner and Lysiak, 2008), high NOX activity in the gonads (and the associated increase in ROS production) may have supressed testosterone synthesis. This would help to explain why the negative relationship between gonadal NOX activity and testosterone levels was stronger in dominant males since the scope for reducing testosterone synthesis would be greater in dominant males.…”
Section: Discussionmentioning
confidence: 99%